Barbiturate derivatives for managing multifaceted oncogenic pathways: A mini review. Issue 3 (18th November 2020) - Prasher, Parteek; Sharma, Mousmee; Singh, Samarth P.; Rawat, Devendra S.
Abstract: Development and progression of metastasis comprises synchronized erroneous expressions of several composite pathways, which are difficult to manage simultaneously with the representative anticancer molecules. The emergence of the drug resistance and the complex interplay between these pathways further potentiates cancer related complexities. Barbiturates and their derivatives present a commendable anticancer profile by attenuating the cancer manifesting metabolic and enzymatic pathways including, but not limited to matrix metalloproteinases, xanthine oxidase, amino peptidases, histone deacetylases, and Ras/mitogen‐activated protein kinase. The derivatization and conjugation of barbiturates with pharmacophores delivers a suitable hybrid profile in containing the anomalous expression of these pathways. The present report presents a succinct collation of the barbiturates and their derivatives in managing the various cancer causing pathways. Abstract :